A reimposition of the death penalty in South Africa - maphosa, motlatso (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2025)
Debates surrounding capital punishment continue to influence criminal justice policy and human rights discourse globally. In South Africa, the Constitutional Court’s landmark judgment in S v. The Death Penalty declared section 277(1)(a) of the Criminal Procedure Act unconstitutional, primarily on the basis of the rights to life, dignity, and equality. Despite the ruling and persistent high levels of violent crime, including sexual offenses and murder, there has been a renewed public and political interest in the possible reinstatement of capital punishment. This paper will undertake a critical and evidence-based examination of this debate within South Africa’s constitutional and criminological context. The analysis focuses on three core concerns that shape the contemporary discourse: the potential for wrongful convictions and the irreversible consequences of execution; the influence of bias, discrimination, and systemic inequality on sentencing outcomes; and international perspectives, particularly the normative positions of the European Union and the United Nations, which consider the death penalty incompatible with evolving human rights standards. Drawing on comparative research, crime data, and international legal developments, the paper assesses whether the reintroduction of the death penalty could have any demonstrable effect on reducing serious violent crime in South Africa. The central aim is to evaluate the criminological claim that capital punishment functions as a deterrent in cases of sexual offenses and murder while critically reflecting on whether such a measure could enhance societal safety within a constitutional democracy. Ultimately, the paper interrogates the tension between demands for harsher punitive measures and South Africa’s commitment to human rights, proportionality, and evidence-based criminal justice policy.